Extreme weather disasters challenges for sustainable development: Innovating a science and policy framework for disaster-resilient and sustainable Quezon City, Philippines. (January 2020) - Raza, Tabassam; Liwag, Carmelita R.E.U.; Andres, Andrea Valentine L.; Castro, Jun T.; Cuña, Aldrin C.; Vinarao, Vincent G.; Raza, Thess Khaz S.; Marasigan, Karl Michael E.; Espinosa, Ramon Iñigo M.; Rentoy, Frederika C.; Perez, Bianca D.; Ahmed, Nisar
Abstract: The cities in Southeast Asian and Small Island Developing States have distorted the natural environment by haphazardly constructing roads, buildings, and other infrastructures. Such massive changes in the environment are altering the ecology, creating sustainable development challenges such as climate-related extreme weather events. Super Typhoon Haiyan devastated portions of Southeast Asia, particularly the Philippines, on November 8, 2013, that caused physical and psychological illnesses to the affected. To prevent these impacts and make cities sustainably develop and Climate Change (CC) resilient, a Science and Policy Framework (SPF) piloting Quezon City Local Government (QCLG) is developed. The application of SPF revealed, among others, the QCLG institutional and personnel adaptive capacities, threat level of CC-related hazards on development growth sectors and institutional and personnel relative vulnerabilities. These findings allowed QCLG to develop sectoral Local Climate Change Action Plan (LCCAP) 2017-2027 to mainstream CC Adaptation (CCA) at the very early stages of development planning. The SPF and LCCAP are flexible and fashioned toward enhancing key development sectors in creating sustainable and CCA-resilient Cities. They can be globally-effective tools for achieving the Paris Agreement, Sustainable Development Goals, and targets of the Sendai Framework.